What Are The Motivational Drivers For Chinese Generation Y Consumers To Consume The International Luxury Brands? - YAO, LIYUE (2015)
Traditionally, there are both extrinsic and intrinsic luxury consumption motivations and people seek for both external and internal values through luxury consumption. The external values include the perceived conspicuous value, unique value and social value. The internal values include the perceived hedonic emotional value and quality value. There has been significant growth of Chinese market for international luxury brands, and Chinese Generation Y consumers are found to have strong appetite for luxury consumption. Therefore, new understanding should move from the general luxury consumption motivations to the specific luxury consumption motivations of Chinese young adults in order to better explore the Chinese young adult market. This article explores what are the specific motivational drivers for Chinese Generation Y consumers to consume the international luxury brands, and if the unique Chinese collectivist culture influence the luxury consumption motivations of Chinese young adults. This research aims to fill the gap between the traditional general luxury consumption motivations and the specific luxury consumption motivations of Chinese Generation Y consumers. An interview approach is used to understand the motivational drivers of luxury consumption from the perspectives of Chinese Generation Y consumers. All interviews are transcribed and recorded, and the real quotes from the interviewees are used in the article when needed in order to improve the authenticity of this study. The findings of this study reveal that the motivational drivers for Chinese Generation Y consumers to consume the international luxury brands are different with the general luxury consumption motivations that have been discussed in the previous literatures. The unique Chinese collectivist culture in terms of face consumption has significant influence on the luxury consumption motivation of Chinese young adults. The implications based on the findings are provided at the end.